Goserelin versus Norethisterone in the Management of Menorrhagia with Uterine Fibroid - Faris A. Rasheed; Jwan N. Sulaiman; Yousif Abdul-Raheem (College of Pharmacy University of Baghdad, 2017)
Menorrhagia is common in patients with uterine fibroids, if operation needs to be delayed for a particular reason, goserelin can be used safely to reduce bleeding and the size of the tumor.The objective is to compare between goserelin acetate and norethisterone on patients with menorrhagia and uterine fibroid. A randomized controlled study conducted in Elwiya maternity teaching hospital, Baghdad from the first of November 2007 to the end of April 2009. 90 patients from the consultant outpatient clinic with menorrhagia and fibroid, and their operations were delayed for medical reason were allocated in two groups, the first group, was given 3.2 mg goserelin acetate subcutaneously monthly for 3 months and the second group was given 5 mg norethisterone orally three times daily during the attack of bleeding and 5 mg once daily, cyclically if no bleeding for 3 months. The fibroid was measured in two dimensions, using convex real-time ultrasound before treatment and three months after treatment. Haemoglobin and the number of pads used were also reported before and after treatment, also the side effects in both groups and the need for operations.The size of fibroid in two dimensions measurement was reduced from 28.24 cm2 ± 6.14 to 12.3 cm2 ± 3.45 in the goserelin group (P=0.0001) versus 26.56 cm2 ± 5.96 to 25.22 cm2 ± 5.01 in the norethisterone group (P= 0.2589). The haemoglobin level was 9.28 gm/100ml ± 2.44 pre-treatment in the goserelin group and 11.2 gm/100ml ± 1.88 post-treatment (P= 0.0001) versus 10.08 gm/100ml ± 2.86, and 10.24 gm/100ml ± 2.46 respectively in the norethisterone group (P= 0.7798). The need for operation was decreased significantly in the goserelin group. Goserelin showed better patient response and reduction in the tumor size than norethisterone in treatment of patients with menorrhagia and uterine fibroids if operation is delayed for medical or other reasons. Key words: Goserelin, Norethisterone , Menorrhagia, Uterine Fibroid